1985
DOI: 10.1584/jpestics.10.491
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Degradation of Fenitrothion in Soils

Abstract: The degradation of fenitrothion (I) and 3-methyl-4-nitrophenol (II), one of the major degradation products in soil, was studied, using 14C preparations labeled at the phenyl ring. In two kinds of aerobic upland soils, I and II degraded with an initial half-life of less than 7 days. A main degradation route of I was a cleavage of the P-O-aryl linkage, leading to the formation of II which underwent further metabolism to 14C02. In soils treated initially with II, a trace amount of 3-methyl-4-nitrocatechol was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
0
12
1
Order By: Relevance
“…Mikami et al reported that 18-22% of the unextracted bound residues was mineralized over a 22-week period using soil with added 14 Cfenitrothion. 13) Although the substituents in the phenyl ring are di erent between I and fenitrothion, a similar degree of mineralization irrespective of solvent extraction suggests that extraction by aqueous organic solvent even in the presence of acid does not signi cantly alter the bioavailability of bound residues. Based on these results, the unextracted bound residues not easily released by the usual extraction with aqueous organic solvent were claried to be mineralized upon their release by microbes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mikami et al reported that 18-22% of the unextracted bound residues was mineralized over a 22-week period using soil with added 14 Cfenitrothion. 13) Although the substituents in the phenyl ring are di erent between I and fenitrothion, a similar degree of mineralization irrespective of solvent extraction suggests that extraction by aqueous organic solvent even in the presence of acid does not signi cantly alter the bioavailability of bound residues. Based on these results, the unextracted bound residues not easily released by the usual extraction with aqueous organic solvent were claried to be mineralized upon their release by microbes.…”
Section: Resultsmentioning
confidence: 99%
“…5,6) e fractions of a pesticide and its metabolites bound to soil may be released over time and become available to plants and soil organisms. Although little is known about the nature of bound residues, 13 C-and 15 N-NMR spectroscopy has been applied to elucidate their chemical nature. [7][8][9] Mineralization experiments of bound residues have also been conducted to examine their bioavailability [10][11][12] and some micro ora showed mineralization ability towards bound residues remaining even a er Soxhlet extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenitrothion-oxon is also a minor metabolite produced by photodegradation of fenitrothion in water or soil. 51,52) Because oxons of organophosphorus insecticides hydrolyze faster than the parent compounds, 44) oxons can be expected to be present only rarely in paddy fields or rivers.…”
Section: Insecticide Metabolitesmentioning
confidence: 99%
“…After application, fenitrothion in the environment is transformed into various compounds by means of biological activity, chemical activity, and photolysis, and many researchers have investigated the resulting transformed products (TPs; Takimoto et al 1976;Spillner et al 1979;Adhya et al 1981;Mikami et al 1985a;Sato 1992;Shalini et al 1996;Alonso et al 1997;Hashizume et al 1997) and their proposed metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%